Анализ методов и результатов измерения выхода изотопа Rn-222 на участке застройки г. Томска; Известия вузов. Физика; Т. 58, № 2/2 - Шилова К. О. Ксения Олеговна; Рыжакова Н. К. Надежда Кирилловна; Ключникова Ю. О. Юлия Олеговна; Иванов М. И. Максим Игоревич; Матюшкина Ю. А. Юлия Андреевна (2015, 2015)
Заглавие с экрана